Legal professional perspectives on barriers and supports for school-aged students and families during reunification from foster care. (December 2019) - Huscroft-D'Angelo, Jacqueline; Trout, Alexandra L.; Henningsen, Christine; Synhorst, Lori; Lambert, Matthew; Patwardhan, Irina; Tyler, Patrick
Highlights: Children and families are not well prepared for reunification . Existing supports are only somewhat effective for the transition period. Mental health supports are most important for children and families. A total of 36 independent barriers were generated for the first question. The biggest barrier is a lack of parental desire to implement long-term changes. A total of 27 unique supports were identified for question two. Effective and accessible supports for families during reunification is necessary. Abstract: Backgroud: Supports following reunification play an important role in successful transitions from out-of-home care to home and school settings for children and their families. There are several stakeholders who play critical roles supporting families during this transition. One key role is tied to legal professionals, who often work closely with the child or family while in care and then continue to monitor family progress during the transition from foster care to the home setting. Although work has been conducted to understand what supports other stakeholders feel children and families need during this transition, little is known about the perspectives of legal professionals. Objective: This exploratory study gathered perspectives from legal professionals regarding the challenges these youths and families face and necessary supports to promote successful reunification. Three research questions guided this work: (1) How prepared do legal professionals feel youth and families are for the reunification period? (2) What do legal professionals perceive as existing barriers for youth and families during reunification? and (3) What services do legal professional perceive as necessary to promote successful reunification and the effectiveness of existing supports? Methods: Participants ( N = 13) completed a brief survey including demographic items and questions on reunification supports following departure from foster care. Participants also engaged in a focus group using the nominal group technique to address two primary questions that addressed challenges faced by families during reunification and necessary supports or services to promote positive youth and family outcomes. Results: Participants felt that families were not well prepared for reunification and that current supports were somewhat effective to support this transition period. They also indicated supports in the mental health domain to be most important. A total of 36 independent barriers were generated for the first question and 27 supports were identified for question two. Conclusion: Establishing effective and accessible supports for families during reunification is necessary for positive family outcomes. This study highlighted barriers in preventing successful reunification, namely limited access to resources and supports in preventing successful reunification and the importance of mental health support for the entire family in promoting successful outcomes.